Home-grown hate : gender and organized racism - Ferber, Abby L., 1966- (Perspectives on gender (New York, N.Y.), 2004)
Home-Grown Hate is an important and timely contribution that advances our understanding of these hate groups, analyzes their movements and sets the agenda in developing strategies to prevent the further proliferation of hate.